2017
DOI: 10.1007/s00335-017-9694-7
|View full text |Cite
|
Sign up to set email alerts
|

Car8 dorsal root ganglion expression and genetic regulation of analgesic responses are associated with a cis-eQTL in mice

Abstract: Carbonic anhydrase-8 (Car8 mouse gene symbol) is devoid of enzymatic activity, but instead functions as an allosteric inhibitor of inositol trisphosphate receptor-1 (ITPR1) to regulate this intracellular calcium release channel important in synaptic functions and neuronal excitability. Causative mutations in ITPR1 and carbonic anhydrase-8 in mice and humans are associated with certain subtypes of spinal cerebellar ataxia (SCA). SCA mice are genetically deficient in dorsal root ganglia (DRG) Car8 expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…In contrast, we demonstrated that murine AAV8-V5-Car8WT showed inhibition of ITPR1-mediated cytosolic calcium release in conjunction with decreased thermal hypersensitivity 6 . We also found that greater DRG Car8 expression antagonizes morphine analgesia concomitant with regulation of morphine-induced ITPR-mediated calcium release 8 . The disadvantage of μ opioids, such as of morphine, is the development of analgesic tolerance seen after morphine administration 14 , which may involve pathways that increase intracellular calcium release such as IP3 binding to IP3 receptors 17 .…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…In contrast, we demonstrated that murine AAV8-V5-Car8WT showed inhibition of ITPR1-mediated cytosolic calcium release in conjunction with decreased thermal hypersensitivity 6 . We also found that greater DRG Car8 expression antagonizes morphine analgesia concomitant with regulation of morphine-induced ITPR-mediated calcium release 8 . The disadvantage of μ opioids, such as of morphine, is the development of analgesic tolerance seen after morphine administration 14 , which may involve pathways that increase intracellular calcium release such as IP3 binding to IP3 receptors 17 .…”
Section: Discussionsupporting
confidence: 55%
“…We constructed vectors containing the WT CA8 cDNA with a V5 tag ( V5-CA8WT ) and CA8 MT cDNA sequence (S100P), which served as a negative control ( V5-CA8MT ) 8 , 9 . We assessed the effects of V5-CA8 overexpression on thermal nociceptive thresholds for 19 days after SN injection and DRG transduction before and after carrageenan injection and inflammation in the hindpaw of naive C57BL/6J mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-four hours before assay, 100K to 250K cells/mL in 1 or 0.5 mL 12 or 24-well plates respectively and then split onto 15 mm glass coverslips (Propper, Long Island, NY) coated with poly-lysine overnight and laminin for 2 h at RT. On the day of the assay, cells were rinsed with perfusate buffer (Buffer 1), 85 then incubated in Buffer 1 containing 0.1 μM Fura-2/AM (Molecular Probes) and 0.012% pluronic F-127 (Sigma) for 45 min at RT (21-22OC) and washed twice with Buffer 1. After another 10 min incubation in Buffer 1 at RT, coverslips were transferred to a RC-42 LP open bath chamber in the QE-1 platform, loaded onto a Leica DMI 6000 B inverted microscope and perfused with Ca2+ free Buffer 2 (Buffer 2, all concentrations in mM: 130 NaCl; 4.7 KCl; 2.3 MgSO4; 5 Glucose; 20 HEPES; 10 EGTA; 1.2 KH2PO4).…”
Section: Methodsmentioning
confidence: 99%